Mental Health Services in Lombardy during COVID-19 outbreak. (June 2020) - Percudani, Mauro; Corradin, Matteo; Moreno, Mauro; Indelicato, Annamaria; Vita, Antonio
Abstract: Lombardy is the Region in Italy the most heavily affected by coronavirus disease (COVID-19) contagion. The Regional Health Authority mandates that mental health services should be guaranteed, identifying mental health as a priority for their citizens. Recommendations for occupational and health safety have been provided to patients and hospital staff, including support for telemedicine activities and remote psychosocial interventions. Services of the Mental Health Departments of Milano "Niguarda" and Brescia "Spedali Civili" Hospitals are providing continued care at a community, residential and hospital level, and to positive COVID-19 psychiatric patients in need of hospitalization.